Intravoxel Incoherent Motion Imaging on Sacroiliitis in Patients With Axial Spondyloarthritis: Correlation With Perfusion Characteristics Based on Dynamic Contrast-Enhanced Magnetic Resonance Imaging - Guo, Chang; Zheng, Kai; Ye, Qiang; Lu, Zixiao; Xie, Zhuoyao; Li, Xin; Zhao, Yinghua (Frontiers in Medicine, 2022)
Background: To prospectively explore the relationship between intravoxel incoherent motion (IVIM) diffusion-weighted imaging (DWI) and dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) parameters of sacroiliitis in patients with axial spondyloarthritis (axSpA). Methods: Patients with initally diagnosed axSpA prospectively underwent on 3.0 T MRI of sacroiliac joint (SIJ). The IVIM parameters (D, f, D*) were calculated using biexponential analysis. Ktrans, Kep, Ve and Vp from DCE-MRI were obtained in SIJ. Uni-variable and multi-variable linear regression analysis were used to evaluate the correlation between the parameters from these two imaging methods after controlling confounders including bone marrow edema (BME), age, agenda, scopes and localization of lesions, course of the disease. And then their correlations were measured by calculating Pearson's correlation coefficient (r). Results: The study eventually enrolled 234 patients (178 males, 56 females; mean age, 28.51±9.50 years) with axSpA. With controlling confounders, D was independently related to Ktrans (regression coefficient [b] = 27.593, P < 0.001), Kep (b = -6.707, P = 0.021), and Ve (b = 131.074, P = 0.003), whereas f and D* had no independent correlation with the parameters from DCE MRI. The correlations above were exhibited with Pearson’s correlation coefficients (r) (r = 0.662, -0.408 and 0.396, respectively, All P < 0.001) Conclusion: There were independent correlations between D derived from IVIM DWI and Ktrans, Kep and Ve derived from DCE-MRI. The factors which affect their correlations mainly included BME, gender and scopes of lesions.